Relevance of mathematics in development scientific and technological thinking - Pacheco Lay, Gonzalo (2014)
The article reviews three issues: Ethos of modern society, notion of time and training strategy through mathematics. The subjects apparently could explain the importance of mathematics in the development of scientific thought and technology in modern societies. From the descriptive empirical evidence, it is understandable strategy, and its results adopted by countries that qualify for better human development.